Enhancing Physics Learning Outcomes through a Reflective Learning Model Supported by Logic Inference Worksheets: A Classroom Action Research Study - Prayogi, Saiful; Miskal, Miskal; Syarifuddin, Syarifuddin; Sukaisih, Roniati (Multi Discere Journal, 2023)
Improving conceptual understanding and reasoning skills in physics requires instructional strategies that go beyond procedural learning. Reflective learning models offer promising frameworks for fostering student engagement, critical thinking, and metacognition. However, the integration of structured reflection with logic-based instructional tools remains underexplored, particularly in middle school physics contexts. This study aims to examine the effectiveness of a reflective learning model supported by logic inference worksheets (LKS) in enhancing student learning outcomes in physics. A classroom action research design was implemented in two cycles at SMPN 18 Mataram, involving 21 students from Class VIII B. Each cycle included the phases of planning, action, observation, and reflection. Data were collected using observation sheets, validated learning outcome tests, and student reflection logs. Instructional improvements were made between cycles based on reflective evaluations. Quantitative results indicated an increase in the average score from 75.15 (Cycle I) to 79.48 (Cycle II), with classical completeness improving from 61.90% to 85.71%. A paired sample t-test confirmed the statistical significance of the gain (t(20) = 4.16, p < 0.001). Qualitative findings revealed improvements in students’ logical reasoning, metacognitive behavior, and classroom engagement. Students demonstrated greater ability to justify answers, articulate reasoning, and collaborate during inference tasks. These outcomes highlight the pedagogical potential of integrating reflective structures and logic-based worksheets in science instruction. The study contributes to reflective pedagogy by offering an evidence-based, adaptable instructional model for developing higher-order thinking skills in physics education.